Data from: Bison grazing in eastern tallgrass prairie does not alter plant diversity after five years ... - Bach, Elizabeth; Chakravorty, Jennifer; Harrington, John A. (Dryad, 2025)
North American tallgrass prairie evolved with regular fire set by Indigenous people and grazing from large herbivores, including the plains bison (Bison bison). In contrast to the uniform effects of prescribed fire, bison graze selectively, creating increased heterogeneity in the landscape. We examined plant community responses to reintroduced bison grazing in high-diversity native and restored tallgrass prairie in Illinois, USA. We evaluated plant community diversity and structure in paired grazed and ungrazed (fenced) plots. After 5 y of grazing at a relatively low target stocking rate of 1 animal unit per 5.2 ha (13 acres), there were no differences in plant community diversity, composition, nonnative: native species ratio, or visual obstruction readings between grazed and ungrazed plots. An interaction exists (or was found) between plant community type and grazing in which grazed savanna plots had greater grass relative abundance compared to ungrazed plots. Ongoing monitoring will evaluate long-term ... : Nachusa Grasslands is located near Franklin Grove, Illinois (41.8837068N, 89.3424108W) and is owned and managed by The Nature Conservancy (TNC). Nachusa consists of more than 1600 ha of native prairie remnants, restored prairies, savannas and woodlands, and wetlands. To examine the impact of bison grazing on plant communities, twenty-two 10 m 3 18 m fenced plots (exclosures) and paired unfenced plots were established prior to bison reintroduction (Fig. 1). Fences are electrified metal wire. The plots are stratified to represent the habitat types at Nachusa (Table 1). There are six sampling sites on native prairie (n=3 in the north unit, n=3 in the south unit), six sampling sites on older plantings (n=3 in the north unit, n=3 in the south unit), four sampling sites on newer plantings (n=3 in the north unit, n=1 in the south unit), and three sampling sites on savannas (n=in the south unit). This unbalanced design results from uneven representation of these habitat types across the preserve. We used a ...